Action research case studies of participatory materials development in two community contexts in Zambia - Lupele, Justin Kalaba (Rhodes University, Faculty of Education, Department of Education, 2003)
This research reports on two action research case studies of participatory materials development in two rural community contexts in Zambia, namely Chiawa and Nalusanga. It aims to explore and articulate the relationships between community-based environmental education and participatory materials development in the WWF Zambia Education Project context; clarify participatory materials development processes by identifying the roles of different 'actors' in these processes and identify and analyse the contextual and other factors that may influence development and use of environmental education materials in rural communities. These aims were explored by means of a number of action research cycles of inquiry in the two communities. The study also articulates the significance of considering ambivalent globalising influences such as international conferences, debates, overseas development aid, national policies and how these shape and influence materials development work in a local context. In order to gain more insight into the local contexts, I developed contextual profiles on the two communities. These capture the contextual factors that influenced the participatory materials development processes. They include issues such as language, ethnicity, literacy, power relations and the local social economy, amongst others. Although this study has been predominately guided by the socially critical orientation to research and education, I have drawn on aspects of other research orientations. I have also explored some of the emerging critiques of the socially critical orientation. The findings of this study reveal the different roles participants can play in participatory materials development; participatory materials development processes as a learning process; the dynamics of participation in an African context; the role of language and literacy in materials development; the need for open-ended process models of learning amongst adult learners and the importance of merging expert and local knowledge in participatory materials development. This study opens up possibilities for further exploration of participatory materials development processes within the WWF ZEP context and beyond.
Keywords: Community development -- Zambia -- Case studies; Environmental education -- Zambia -- Case studies; Sustainable development -- Zambia -- Case studies